Active Compound Identification in Extracts of N. lappaceum Peel and Evaluation of Antioxidant Capacity - Mariel Monrroy; Onix Araúz; José Renán García (Journal of Chemistry)
Nephelium lappaceum and its by-products have great potential in the agricultural, pharmaceutical, and food industries. Some studies have shown that N. lappaceum by-products exhibit antimicrobial, antioxidant, antidiabetic, and anticancer properties. However, studies focused on identifying these compounds are rare. The availability of polyphenolic compounds can vary according to environmental conditions, soil, plant variety, and agronomic management. Therefore, in this study, the active compounds in extracts of the N. lappaceum peel were identified, and their antioxidant properties were evaluated using various extraction solvents and both ultrasonic and boiling extraction techniques. The chemical characterization of the N. lappaceum peel exhibited carbohydrate and reducing sugar contents of 12 and 2%, respectively. Phytochemical analysis indicated the presence of flavonoids, tannins, terpenes, and steroids. The total phenolic and flavonoid contents and total antioxidant capacity were the highest in the hydroethanolic extract obtained by ultrasound, with values of 340 mg gallic acid equivalents g−1, 76 mg quercetin equivalents g−1, and 2.9 mmol of Trolox equivalents g−1, respectively. Contrarily, the total anthocyanin content was higher in the acid extract obtained by ultrasound, with a value of 0.7 mg cyanidin-3-O-glucoside equivalents g−1. A total of 18 compounds—including hydroxybenzene, phenolic acid, flavonoids, fatty acids (saturated, unsaturated, and ester), vitamin, arenecarbaldehyde, and phthalate—were identified for the first time in the N. lappaceum peel using gas chromatography-mass spectrometry. The identified compounds have been previously isolated from other plants and reportedly exhibit anticancer, anti-inflammatory, antimicrobial, and antioxidant activities. Thus, the N. lappaceum peel was shown to be a potential source of bioactive compounds of immense importance in the pharmacological and food industries.